Harnessing Artificial Intelligence-Chat GPT (Generative Pretrained Transformer) to engage youths and women in climate-smart, sustainable livestock farming - Ekule, Muluken; Wamatu, Jane (International Center for Agricultural Research in the Dry Areas, 2023)
Harnessing Artificial Intelligence-Chat GPT (Generative Pretrained Transformer) to engage youths and women in climate-smart, sustainable livestock farming.